Grupos escolares rurais na antiga Usina Tamoio (Araraquara/SP) - Flores, Ana Flávia (Universidade Federal de São Carlos, 2015)
The aim of this work is to investigate the creation of the School Groups in rural areas in the state of São Paulo, in 1930, a period that starts and shows the materialization of rural school groups. Emphasizing a case study in the former Plant Tamoio in Araraquara / SP. In Plant Tamoio since the decades from 1930 to 1940 there were isolated schools that were scattered in the various sections of the plant site. And three rural school groups. The first School D. Giannina Morganti made in 1935, located at the headquarters of the Plant, the second School Group Commander Peter Morganti established in 1942, located in Bela Vista Section and the third School Group "Captain Domingos Soares de Barros," organized in 1947 was in Section Alligator. Between the decade of 1930-1940 that the legal consolidation for the creation and expansion of rural schools happen. As documentary sources chosen to rebuild the stories of three school groups we used the following sources for this research: the Araraquara School Reports 1936 and 1940; the Yearbook of São Paulo State Education 1936; Federal legislation of 1934 and 1937; State law 1933, 1935, 1938 and 1947 which provides for rural primary schools. Important sources in implementations of some government policies on the issue of rural primary education. Information about the school groups of Tamoio plant were found in the following files: Book Movement Map; Commitment Term Paper; Book of final exams; Book of Business Terms; Book of Enrollment (all from 1935 to 1949; 1942 to 1949, a period corresponding to the year of installation of the plant of school groups) to e Araraquara Album 1948. The survey results show that the design of school groups in Tamoio plant was related to formation of a national identity, training and continuing to work in the industrial complex. And especially, the Rural School Groups played an important role within the state development project to combat foreignness, since the large farms in the interior received workers of other nationalities.
Keywords: Grupos Escolares; Grupos Escolares Rurais e Usina Tamoio; School groups; Rural School Groups and Plant Tamoio; CIENCIAS HUMANAS::EDUCACAO